Unveiling the speech acts employed in an aggressive Nigerian Christian prayers sessions - Kenneth Ekezie Obiorah; Patience Nonye Edeoga (Yayasan Mitra Persada Nusantara, 2026)
Humans perform speech act when they speak or write. These acts enhance discourse and conversation. This study explores the types of speech acts performed during energetic prayer sessions in a Nigeria church and the linguistic strategies employed in performing these acts. Data were gathered from 12 months research visit to the of Mountain of Fire and Miracles Ministry Headquarter church in Lagos, Nigeria. Through a qualitative analysis of prayer language, the research identifies various speech acts used to inspire spiritual fervor during prayer sessions. The speech acts identified include: commanding, requesting, denying of efforts, questioning, promising and making positive assertions. Findings reveal that the illocutionary forces of the speech acts were felicitous because they amplify spiritual intensity, foster a sense of community, and promote vibrant prayer experiences. The result demonstrates that language plays a vital role in shaping spiritual practices and experiences within the mountain of fire and miracles ministry.